Quantifying Phraseological Style in Two Modern Chinese Versions of Don Quijote - Ji, Meng (Meta, 2008)
AbstractQuantifying style, or stylometry, has always been one of the oldest traditions in Western literary studies. It seems, however, that such a well-explored and long-standing scientific methodology has been rarely applied to translations, as opposed to original literary texts. The present paper, which focuses on the stylistic use of phraseology in two contemporary Chinese versions of Cervantes’ Don Quijote, shall endeavour to address the two current problems in corpus-based translation stylistics, i.e., the lack of debate on the question of semantically-rich linguistic units in quantifying style of translations, and the need for testing the use of methods and techniques adapted from corpus statistics in detecting stylistic traits in translations. It is hoped that this study, which aims at expanding the current methodological framework for translation stylistics, will help in the development of this growing area of research in Translation Studies.